Associations of maternal age with outcomes in very low birth weight singleton infants: a retrospective study - Sun, Junfang; Sun, Mengya; Zhang, Lulu; Lai, Chunchi; Jiang, Hong (Frontiers in Pediatrics, 2025)
BackgroundWith advances in perinatal medicine, there has been a rise in the preterm birth rate, especially the rate of very low birth weight (VLBW) and extremely low birth weight infants. Studies have shown that maternal age during pregnancy and at the time of delivery is associated with pregnancy complications and poor neonatal outcomes. Little is known about the effect of maternal age on the outcome of very low birth weight infants.ObjectivesTo investigate the effects of maternal age on the adverse outcomes of singleton very low birth weight neonates.MethodsWe used data of VLBW infants from the neonatal database of our hospital. Maternal age was categorized as 20–24, 25–34 (reference group), 35–39 and ≥40 years. Statistical analyses included univariate and multivariate logistic regression analysis.ResultsThe study ultimately included 603 singleton, very low birth weight infants. After adjustment, neonatal outcomes in the group of older mothers were similar to those of the reference group for bronchopulmonary dysplasia, necrotizing enterocolitis, respiratory distress syndrome, severe asphyxia, retinopathy of prematurity and intraventricular hemorrhage grades 3–4. In the 20–24 year age group higher odds were present for sepsis [Odds ratio (OR) = 6.021; 95% confidence interval (CI), 1.741–20.818, p < 0.05] and for mortality (OR = 7.784; 95% CI, 2.198–27.568, p < 0.05). Higher odds for asphyxia (OR = 1.891; 95% CI, 1.238–2.890, p < 0.05) and death (OR = 2.101, 95% CI, 1.004–4.395, p < 0.05) were observed in infants of mothers in the 35–39 year age group. The incidence of sepsis was significantly higher in the age group of ≥40 years (OR = 2.873; 95% CI, 1.186–6.958, p < 0.05).ConclusionsIn singleton very low birth weight neonates, neonatal outcomes were associated with maternal age, and adverse outcomes were more pronounced in infants of advanced maternal age (AMA) mothers.